Hybrid Pd0.1Cu0.9Co2O4 nano-flakes: a novel, efficient and reusable catalyst for the one-pot heck and Suzuki couplings with simultaneous transesterification reactions under microwave irradiation - Patel, Ashok Raj; Maity, Gurupada; Pati, Tanmay K.; Adak, Laksmikanta; Cioffi, Christopher L.; Banerjee, Subhash (Frontiers in Chemistry, 2024)
We report the fabrication of a novel spinel-type Pd₀.₁Cu₀.₉Co₂O₄ nano-flake material designed for Mizoroki-Heck and Suzuki coupling-cum-transesterification reactions. The Pd₀.₁Cu₀.₉Co₂O₄ material was synthesized using a simple co-precipitation method, and its crystalline phase and morphology were characterized through powder XRD, UV-Vis, FESEM, and EDX studies. This material demonstrated excellent catalytic activity in Mizoroki-Heck and Suzuki cross-coupling reactions, performed in the presence of a mild base (K₂CO₃), ethanol as the solvent, and microwave irradiation under ligand-free conditions. Notably, the Heck coupling of acrylic esters proceeded concurrently with transesterification using various alcohols as solvents. The catalyst exhibited remarkable stability under reaction conditions and could be recycled and reused up to ten times while maintaining its catalytic integrity.